Does molar-incisor hypomineralization (MIH) affect only permanent first molars and incisors? New observations on permanent second molars - de Farias, Aline Leite [UNESP]; Rojas-Gualdrón, Diego Fernando; Girotto Bussaneli, Diego [UNESP]; Santos-Pinto, Lourdes [UNESP]; Mejía, Juan Diego; Restrepo, Manuel [UNESP] (Wiley, 2021)
Background: The second permanent molar plays an important role when considering extraction of first permanent molars severely affected by molar-incisor hypomineralization (MIH). Aim: To assess the association between MIH and enamel hypomineralization of the second permanent molars in terms of presence and severity. Design: In this retrospective cross-sectional study, permanent teeth were evaluated in 453 patients between the ages of 13 and 16 at a dental clinic, using intraoral photographs. A calibrated examiner classified enamel hypomineralization using the MIH index and dental caries experience using the DMFT and DMFS indices. Statistical analyses were performed using a linear generalized model and ordinal logistic regression. Results: The most commonly affected teeth by enamel hypomineralization were permanent molars, whereas incisors, premolars, and canines were less affected. The presence of severe defects in the first permanent molars was associated with mild defects in the second permanent molars (OR = 4.01; 95% CI: 2.50-7.77). Enamel hypomineralization was associated with increased caries experience (PR = 5.54; 95% CI: 3.81-9.06). Conclusion: Enamel hypomineralization mainly affects the first and second permanent molars. Mild defects in the second permanent molars tend to be more frequent in patients with severe MIH in the first permanent molars. The presence of enamel hypomineralization was associated with higher dental caries experience.
Keywords: dental caries; dental enamel; hypomineralization; molar; tooth eruption